The Angola Gyre is a hotspot of dinitrogen fixation in the South Atlantic Ocean - Tanya Marshall; Julie Granger; Karen L. Casciotti; Kirstin Dähnke; Kay-Christian Emeis; Dario Marconi; Matthew R. McIlvin; Abigail E. Noble; Mak A. Saito; Daniel M. Sigman; Sarah E. Fawcett (Communications Earth & Environment, 2022)
Between 28 and 100% of nitrogen fixation in the South Atlantic occurs within the Angola Gyre and is potentially fuelled by supply of bioavailable iron from margin sediments and excess phosphorus, according to an analysis of observational hydrographic data and nitrate isotope ratios.